2021
DOI: 10.3390/jof7050391
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Ecological Role and Biotechnological Potential of Antarctic Marine Fungi

Abstract: The Antarctic Ocean is one of the most remote and inaccessible environments on our planet and hosts potentially high biodiversity, being largely unexplored and undescribed. Fungi have key functions and unique physiological and morphological adaptations even in extreme conditions, from shallow habitats to deep-sea sediments. Here, we summarized information on diversity, the ecological role, and biotechnological potential of marine fungi in the coldest biome on Earth. This review also discloses the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 254 publications
(301 reference statements)
3
17
0
Order By: Relevance
“…In particular, we found 12 ASVs affiliating to nine genera, including genera commonly encountered in a variety of benthic deep-sea ecosystems (e.g., Aspergillus; [24,32]) and polar systems (e.g., Naganishia, Dothideomycetes and Agaricomycetes; [27,74,75]). Fungi belonging to the genera Trichoderma found in this study were already reported and isolated from lake and sediments of the Penguin Island in Antarctica [76,77], while other genera commonly found in Antarctic sediments, such as Metschnikowia, Galciozyma and Psedogymnoascus, were not encountered (for a more detailed list see [28]). Furthermore, other fungal taxa, including members belonging to Fusarium and Wickerhamomyces, have been reported to be associated with Antarctic sponges and macroalgae [78][79][80], while taxa affiliated with Exophiala and Aspergillus have been previously isolated from different Antarctic marine samples [28,81].…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In particular, we found 12 ASVs affiliating to nine genera, including genera commonly encountered in a variety of benthic deep-sea ecosystems (e.g., Aspergillus; [24,32]) and polar systems (e.g., Naganishia, Dothideomycetes and Agaricomycetes; [27,74,75]). Fungi belonging to the genera Trichoderma found in this study were already reported and isolated from lake and sediments of the Penguin Island in Antarctica [76,77], while other genera commonly found in Antarctic sediments, such as Metschnikowia, Galciozyma and Psedogymnoascus, were not encountered (for a more detailed list see [28]). Furthermore, other fungal taxa, including members belonging to Fusarium and Wickerhamomyces, have been reported to be associated with Antarctic sponges and macroalgae [78][79][80], while taxa affiliated with Exophiala and Aspergillus have been previously isolated from different Antarctic marine samples [28,81].…”
Section: Resultssupporting
confidence: 57%
“…Fungi belonging to the genera Trichoderma found in this study were already reported and isolated from lake and sediments of the Penguin Island in Antarctica [76,77], while other genera commonly found in Antarctic sediments, such as Metschnikowia, Galciozyma and Psedogymnoascus, were not encountered (for a more detailed list see [28]). Furthermore, other fungal taxa, including members belonging to Fusarium and Wickerhamomyces, have been reported to be associated with Antarctic sponges and macroalgae [78][79][80], while taxa affiliated with Exophiala and Aspergillus have been previously isolated from different Antarctic marine samples [28,81]. Such a comparison suggests that Antarctic deep-sea sediments can host profoundly different fungal assemblages depending on specific environmental and ecological settings.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The recent application of molecular approaches has revealed far more diverse and abundant marine fungi than those previously studied, with a growing body of evidence for their biogeochemical and ecological functions [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, fungi isolated from marine or marine-related habitats are producers of several bioactive compounds [ 7 , 25 , 26 , 27 , 28 , 29 , 30 ], which can open up a new era of drug research. Nevertheless, marine fungi remain one of the most under-studied microbial groups, with 95% of the ocean remaining mycologically unexplored [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The marine environment covers approximately 70% of the Earth's surface and represents an enormous pool of biodiversity resources [1][2][3]. Marine microorganisms possess the potential for several biotechnological and industrial applications and play an important ecological role [4,5]. The last decades have witnessed numerous studies in the natural metabolites derived from marine creatures or their associated microorganisms [6][7][8].…”
Section: Introductionmentioning
confidence: 99%